2011
DOI: 10.1080/1478646x.2010.509498
|View full text |Cite
|
Sign up to set email alerts
|

Studies of mixed reductant systems with Azur A as photosensitizer for solar energy conversion and storage in photogalvanic cells

Abstract: Purpose: The role of mixed reductant systems in photogalvanic cells was studied in a photogalvanic system containing Azur A as photosensitizer, EDTA as reductant, which was mixed with dextrose, NTA and oxalic acid, respectively, for increasing the conversion efficiency and storage capacity of photogalvanic cells.Design/methodology/approach: This research presents an interesting photogalvanic system for improvement of conversion efficiency and storage capacity to reduce the cost of construction and ensure comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Madhwani et al [18][19][20] have used fuschin basic, rose bengal and fluorescein-ethylenediaminetetraacetic acid systems, in photogalvanic cells for solar energy conversion and storage. The effect of using two reductants in photogalvanic cells has been reported by Dubey [21], Gangotri and Indora [22], and Gangotri et al [23], while the use of two dyes in photogalvanic cells has been reported by Gangotri and Lal [24], and Lal and Yadav [25].…”
Section: Introductionmentioning
confidence: 92%
“…Madhwani et al [18][19][20] have used fuschin basic, rose bengal and fluorescein-ethylenediaminetetraacetic acid systems, in photogalvanic cells for solar energy conversion and storage. The effect of using two reductants in photogalvanic cells has been reported by Dubey [21], Gangotri and Indora [22], and Gangotri et al [23], while the use of two dyes in photogalvanic cells has been reported by Gangotri and Lal [24], and Lal and Yadav [25].…”
Section: Introductionmentioning
confidence: 92%
“…A search of literature (Gangotri and Regar, 1997;Gangotri et al, 1999;Gangotri and Lal, 2000;Gangotri and Meena, 2001;Gangotri and Genwa, 2004;Gangotri and Lal, 2005;Chauhan et al, 2006) reveals that different photosensitizers and reductants have been used in photogalvanic cells. We have studied the use of EDTA-new methylene blue C safranine O system in photogalvanic cell for solar energy conversion and storage.…”
Section: Introductionmentioning
confidence: 96%
“…Mixed dyes (combination of two dyes) were used to use the broad solar spectrum of visible region of solar radiation for generation of better electrical output [18, 19]. An enhancement in electrical output of the cell consisting of mixed dyes was observed when compared with the cell with single dye [20]. Absorption spectra of single and mixed dyes are shown in Figures 1a–1c.…”
Section: Introductionmentioning
confidence: 99%